Anticancer Potential of Citrus Juices and Their Extracts: A Systematic Review of Both Preclinical and Clinical Studies - Cirmi, Santa; Maugeri, Alessandro; Ferlazzo, Nadia; Gangemi, Sebastiano; Calapai, Gioacchino; Schumacher, Udo; Navarra, Michele (Frontiers in Pharmacology, 2017)
Background: during the last decades, a huge body of evidence has been accumulated suggesting that Citrus fruits and their juices might have a role in preventing many diseases including cancer. Objective: to summarize the numerous evidences on the potential of Citrus juices and their extracts as anticancer agents. Data sources: a systematic review of articles written in English using MEDLINE (1946-present), EMBASE (1974-present) and Web of Sciences (1970-present) was performed independently by two reviewers. Search terms included Citrus, Citrus aurantifolia, Citrus sinensis, Citrus paradisi, Citrus fruits, Citrus fruits extract, cancer, neoplasm, neoplasia, tumor, metastasis, carcinogenesis, proliferation. The last search was performed on March 16th, 2017. Study selection: study selection and systematic review were carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Prior to the beginning of the review, Authors defined a checklist for inclusion criteria, thus including articles which meet the following: i) published on peer-reviewed scientific journals; ii) Citrus juice used alone; iii) extracts derived from Citrus juice; iii) for preclinical studies, an exposure time to Citrus juices and their extracts more than 24 h. Reviews, meta-analyses, conference abstracts and book chapters were excluded. Data extraction: three reviewers independently performed the extraction of articles. Data synthesis: 22 papers met our inclusion criteria and were eligible for inclusion in the final review. According to the kind of study, the selected ones were further divided in preclinical (n=20) and observational (n=2) studies. Conclusion: the studies discussed in this review strongly corroborate the role of Citrus juices and their derivatives as potential resource against cancer.